Підвищення надійності кіл опалення електровозів ЧС4 та ЧС8 - Маренич, О.О. (Електротехніка і електромеханіка, 2011)
Power contact fusing currents for 7SP1 and 1SVAD8 contactors used in heating circuits of electric locomotives have been determined. It has been shown that in operation there may be situations when short-circuit currents are significantly greater than fusing currents. In this condition, a short-circuit current goes through the contactors contacts before protection actuation over a period of time long enough for the contacts fusion resulted from insufficient thermal stability current. Recommendations for thermal stability current values in the heating circuits have been developed.